Performing the intercultural city - Knowles, Richard Paul, 1950- (Theater--theory/text/performance., 2017)
"Performing the Intercultural City explores how Toronto--a representative global city in the first country in the world to adopt a policy of official multiculturalism--stages its diversity through its many intercultural theater companies and troupes. By examining the ways in which Indigenous, Filipino, Latino/a and Afro-Caribbean Canadian theater in Toronto has developed play structures based on culturally specific forms of expression, Performing the Intercultural City analyzes the ways in which theater companies from a variety of marginalized communities of color in Toronto have worked across cultural difference to produce a new kind of intercultural performance"--